2018
DOI: 10.1073/pnas.1720493115
|View full text |Cite
|
Sign up to set email alerts
|

Role of sodium channel subtype in action potential generation by neocortical pyramidal neurons

Abstract: Neocortical pyramidal neurons express several distinct subtypes of voltage-gated Na channels. In mature cells, Na1.6 is the dominant channel subtype in the axon initial segment (AIS) as well as in the nodes of Ranvier. Action potentials (APs) are initiated in the AIS, and it has been proposed that the high excitability of this region is related to the unique characteristics of the Na1.6 channel. Knockout or loss-of-function mutation of the gene is generally lethal early in life because of the importance of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 62 publications
5
90
0
Order By: Relevance
“…4C). In summary, these measurements represent a general improvement from previous estimates of the Na + influx in the AIS, associated with APs, using the indicator ANG-2 (Miyazaki & Ross 2015;Miyazaki et al 2019) or the less sensitive indicator SBFI (Kole et al 2008;Fleidervish et al 2010;Baranauskas et al 2013;Scott et al 2014;Katz et al 2018). But the significant and critical improvement of the present measurements is that they were achieved at the unprecedented temporal resolution of 10 kHz.…”
Section: Quantification Of the Spatial Profile Of Na + Concentrationsupporting
confidence: 49%
See 2 more Smart Citations
“…4C). In summary, these measurements represent a general improvement from previous estimates of the Na + influx in the AIS, associated with APs, using the indicator ANG-2 (Miyazaki & Ross 2015;Miyazaki et al 2019) or the less sensitive indicator SBFI (Kole et al 2008;Fleidervish et al 2010;Baranauskas et al 2013;Scott et al 2014;Katz et al 2018). But the significant and critical improvement of the present measurements is that they were achieved at the unprecedented temporal resolution of 10 kHz.…”
Section: Quantification Of the Spatial Profile Of Na + Concentrationsupporting
confidence: 49%
“…Experimental approaches for the investigation of Na + influx in the intact AIS during AP generation include the voltage-clamp patch electrode technique (Yue et al 2005;Carter & Bean, 2009;Katz et al 2018) and the optical recording of fluorescence from Na + indicators (Kole et al 2008;Fleidervish et al 2010; Baranauskas et al 2013;Miyazaki & Ross, 2015;Katz et al 2018;Miyazaki et al 2019). The first approach allows recording fast Na + currents triggered by artificial somatic injections of voltage waveforms mimicking an AP, with no information on the spatial organisation of the current and limitations due to space-clamp problems (Bar-Yehuda & Korngreen, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without this increase in levels of WT VGSCs at the nodes of Ranvier, the Scn8a Δ9/Δ9 and Scn8a ∇3/∇3 homozygous mutants would demonstrate impaired nerve conduction. Though additional Western blotting and immunostaining would be necessary to confirm this hypothesis, previous studies have demonstrated that loss of Scn8a expression leads to the compensatory recruitment of other VGSC proteins, particularly Na v 1.2 (encoded by Scn2a ), to the mature nodes of Ranvier and axon initial segment . In further support of this hypothesis, Vega et al reported that Na v 1.2 protein levels are significantly upregulated in null Scn8a med‐Tg/med‐Tg mutants relative to WT littermates …”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, a recent study investigating AP initiation in Na V 1.6null pyramidal neurons demonstrated that the Na V 1.6 subtype is not necessary for the lower firing threshold at the AIS compared to the soma (Katz et al, 2018). Rather, the authors suggest that the hyperpolarizing shift in the activation of axonal sodium channels might be a result of molecular interactions within the AIS.…”
Section: Ais -The Site Of Ap Initiationmentioning
confidence: 99%